Guilty mind in sexual crimes - Mohamad Yunus, Mohamad Ismail; Mohamad Hanifa, Shamshina (Universiti Tun Hussein Onn Malaysia, 2017)
“Actus non facit reum nisi mens sit rea” which means an act does not constitute crime unless done with a guilty mind. A reasonable man is viewed as a moral agent and not simply as an instrument of causing harm. He is regarded as responsible for his actions. Being a responsible agent means that man is capable of reason (right-thinking person); he is capable of understanding the social and legal norms to which he is subjected; he possesses free will. He can thus control his actions and can choose whether to comply with the law or not. Several statutory provisions do not expressly contain any specific provision for mental element (mens rea) in proving crimes committed. Nowhere in the Penal Code or elsewhere is there any general provision endorsing the doctrine of mens rea. Does this mean that liability in all such cases must be considered "strict" in the sense that no mental element or other criterion of blameworthiness need be established? For example, the offence of rape carrying a maximum to twenty years imprisonment under section 376 (1) makes no reference to any mental element. What is position of an accused who honestly believes that the woman is consenting to sexual intercourse when in fact she is not? And what of the accused who honestly thinks the girl is over 16 years of age when in fact she is not? Must such an accused person be convicted on the basis that the doctrine of mens rea is inapplicable under the Penal Code? This book discusses the issue and other related matters on mens rea comparatively and it is necessary reference for the various parties involved in the administration of criminal justice including students studying the subject of criminal law and evidence.